Measures to Ensure Employment in Uzbekistan Through the Support of Small Business and Entrepreneurship - Narmanov Ulugbek Abdugapparovich (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
The article discusses the problems of small business and entrepreneurship in Uzbekistan and employment through the establishment of new small enterprises and micro-firms, as well as the role and importance of small business in the further development of economic potential, employment promotion and development of mechanisms to increase direct income. The development of the economy, the liberalization of entrepreneurial activity in addressing issues related to the creation of new jobs, increasing employment, the development of local industries based on the efficient use of local resources. The issues of improving the export potential of the country, taking measures to further increase the importance of this small business and entrepreneurship, the organization of production on the basis of local resources, require less investment, ie allow them to quickly adapt to market conditions.